Short-term variations in particulate matter flux in Terra Nova Bay, Ross Sea - FABIANO M; CATTANEO VIETTI R; PUSCEDDU A; ALBERTELLI G.; CHIANTORE, MARIACHIARA; POVERO, PAOLO; MISIC, CRISTINA (-Cambridge University Press / New York:40 West 20th Street:New York, NY 10011:(800)872-7423, (212)924-3900, EMAIL: journals_subscriptions@cup.org, INTERNET: http://www.journals.cambridge.org, Fax: (212)691-3239 -Oxford: Blackwell Scientific Publications., 1997)
As part of the Ross Sea Marginal Ice Zone Ecology Project (ROSSMIZE) the summer organic matter flux through the water column was measured at 40 m depth in Terra Nova Bay. Water samples and material from a sediment trap on the sea-bottom were analysed for their biochemical composition. A close coupling between biochemical composition of the organic matter in the water column and the material collected in the sediment trap was found, resulting from complex interactions between physical and biological processes. The physical processes are related to break-up and melting of the ice cover and occur mainly in the early summer season, whilst biological processes play a key role in mid summer and, from the evidence from faecal pellets, are related to the primary production and consumption processes.